2021
DOI: 10.3389/fgene.2021.702540
|View full text |Cite
|
Sign up to set email alerts
|

Differential lncRNA/mRNA Expression Profiling and Functional Network Analyses in Bmp2 Deletion of Mouse Dental Papilla Cells

Abstract: Bmp2 is essential for dentin development and formation. Bmp2 conditional knock-out (KO) mice display a similar tooth phenotype of dentinogenesis imperfecta (DGI). To elucidate a foundation for subsequent functional studies of cross talk between mRNAs and lncRNAs in Bmp2-mediated dentinogenesis, we investigated the profiling of lncRNAs and mRNAs using immortalized mouse dental Bmp2 flox/flox (iBmp2fx/fx) and Bmp2 knock-out (iBmp2ko/ko) papilla cells. RNA sequencing was implemented to study the expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…Both CIN and cervical cancer are known to be associated with HPV infection, which can be considered as the early lesion of cervical cancer[ 23 , 24 ]. The transformation of CIN to cervical cancer requires a process, but not all CIN will transition to high-risk areas; some CIN patients can return to normal state[ 25 , 26 ] through autoimmune regulation without surgical treatment. The clinical morphological evaluation method is commonly used for the clinical morphological evaluation method of cervical lesions[ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both CIN and cervical cancer are known to be associated with HPV infection, which can be considered as the early lesion of cervical cancer[ 23 , 24 ]. The transformation of CIN to cervical cancer requires a process, but not all CIN will transition to high-risk areas; some CIN patients can return to normal state[ 25 , 26 ] through autoimmune regulation without surgical treatment. The clinical morphological evaluation method is commonly used for the clinical morphological evaluation method of cervical lesions[ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of E6 and E7 resulted in the detection of many DEGs using RNA-seq and RT-qPCR. Fourteen of these hub genes were linked to cell adhesion ( Chute, 2006 ; Teicher and Fricker, 2010 ; Paolillo and Schinelli, 2019 ; Marotta et al, 2021 ), leukocyte–endothelial migration ( Yakovlev et al, 2019 ; Morein et al, 2020 ; Yan et al, 2021 ), stem cell signaling ( Davidson et al, 2007 ; Bijlmakers, 2009 ), and epithelial–mesenchymal transition ( Pastushenko et al, 2021 ; Wang et al, 2021 ). Based on these experimental and bioinformatics analyses, we hypothesized that HPV16 E6 and E7 signaling causes differential mRNA expression through direct or indirect mRNA pathways that regulate cell adhesion and chemokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing prevalence of Illumina technology in recent years, RNA-sequencing (RNA-Seq) technology has been effectively used in biomedical research ( Tao et al, 2021 ; Wang et al, 2021 ). The carcinogenetic effect of E6 and E7 is apparent, but molecules that are induced by these proteins in HaCaT cells still need to be researched, and high-throughput sequencing would contribute vastly to this question.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of Bmp-2, Bmp-4, Bmp-7, and Bmp-9 causes severe impairment of dentinogenesis, enlarged dental pulp cavity, wide predentin, thin dentin, tooth attrition, delayed root eruption, and impairment of odontoblast differentiation [ 33 , 34 , 36 , 37 , 38 , 43 , 44 , 46 , 47 , 299 , 300 , 301 , 302 ]. Using bioinformatics software, this study showed that the Bmp-2 signal regulates cell differentiation, transcriptional regulation, and developmentally relevant signaling pathways [ 303 ]. Teeth in mice lacking Bmp-2, Bmp-4, and Bmp-9 showed reduced tooth-related gene expression, including phosphorylated Smad1/5/8, Alp, Collα1, Dlx3, Dmp1, Dspp, Osx, and Runx2 [ 32 , 36 , 37 , 38 , 39 , 46 , 47 , 302 ].…”
Section: Bmp Signaling During Tooth Developmentmentioning
confidence: 99%